Magnetic Field Effect on Poiseuille Flow and Heat Transfer of Carbon Nanotubes along a Vertical Channel Filled with Casson Fluid - Aman, Sidra; Khan, Ilyas; Zulkhibri, Ismail; Mohd Zuki, Salleh; Alshomrani, Ali Saleh; Alghamdi, Metib Said (American Institute of Physics, 2017)
Applications of carbon nanotubes, single walls carbon nanotubes (SWCNTs) and multiple walls carbon nanotubes (MWCNTs) in thermal engineering have recently attracted significant attention. However, most of the studies on CNTs are either experimental or numerical and the lack of analytical studies limits further developments in CNTs research particularly in channel flows. In this work, an analytical investigation is performed on heat transfer analysis of SWCNTs and MWCNTs for mixed convection Poiseuille flow of a Casson fluid along a vertical channel. These CNTs are suspended in three different types of base fluids (Water, Kerosene and engine Oil). Xue [Phys. B Condens. Matter 368, 302–307 (2005)] model has been used for effective thermal conductivity of CNTs. A uniform magnetic field is applied in a transverse direction to the flow as magnetic field induces enhancement in the thermal conductivity of nanofluid. The problem is modelled by using the constitutive equations of Casson fluid in order to characterize the non-Newtonian fluid behavior. Using appropriate non-dimensional variables, the governing equations are transformed into the non-dimensional form, and the perturbation method is utilized to solve the governing equations with some physical conditions. Velocity and temperature solutions are obtained and discussed graphically. Expressions for skin friction and Nusselt number are also evaluated in tabular form. Effects of different parameters such as Casson parameter, radiation parameter and volume fraction are observed on the velocity and temperature profiles. It is found that velocity is reduced under influence of the exterior magnetic field. The temperature of single wall CNTs is found greater than MWCNTs for all the three base fluids. Increase in volume fraction leads to a decrease in velocity of the fluid as the nanofluid become more viscous by adding CNTs.